Globalizing world ? culture,economics,politics - Held, David (Ed.) (London, 2000)
The news media today are full of references to globalization - the complex connections between different countries in the world and the way these are increased over time. It is becoming a contemporary cliche that we live in a world of globalization, but little attention is paid to how it actually works in people's lives. A Globalizing World? offers a clear and intelligible guide to one of the key debates of our time, introducing the main theoretical positions to examine globalization in practice, from the films we watch to the jobs that are available to us and the goods we buy to the way we are governed.
Keywords: national security-social aspects